Safety and efficacy of mesenchymal stromal cells mitochondria transplantation as a cell-free therapy for osteoarthritis - Ana Maria Vega-Letter; Cynthia García-Guerrero; Liliana Yantén-Fuentes; Carolina Pradenas; Yeimi Herrera-Luna; Eliana Lara-Barba; Felipe A. Bustamante-Barrientos; Masyelly Rojas; María Jesús Araya; Nicole Jeraldo; Constanza Aros; Francisca Troncoso; et al. (Journal of Translational Medicine)
Abstract Objective The inflammatory responses from synovial fibroblasts and macrophages and the mitochondrial dysfunction in chondrocytes lead to oxidative stress, disrupt extracellular matrix (ECM) homeostasis, and accelerate the deterioration process of articular cartilage in osteoarthritis (OA). In recent years, it has been proposed that mesenchymal stromal cells (MSC) transfer their functional mitochondria to damaged cells in response to cellular stress, becoming one of the mechanisms underpinning their therapeutic effects. Therefore, we hypothesize that a novel cell-free treatment for OA could involve direct mitochondria transplantation, restoring both cellular and mitochondrial homeostasis. Methods Mitochondria were isolated from Umbilical Cord (UC)-MSC (Mito-MSC) and characterized based on their morphology, phenotype, functions, and their ability to be internalized by different articular cells. Furthermore, the transcriptional changes following mitochondrial uptake by chondrocytes were evaluated using an Affymetrix analysis, Lastly, the dose dependence therapeutic efficacy, biodistribution and immunogenicity of Mito-MSC were assessed in vivo, through an intra-articular injection in male C57BL6 mice in a collagenase-induced OA (CIOA) model. Results Our findings demonstrate the functional integrity of Mito-MSC and their ability to be efficiently transferred into chondrocytes, synovial macrophages, and synovial fibroblasts. Moreover, the transcriptomic analysis showed the upregulation of genes involved in stress such as DNA reparative machinery and inflammatory antiviral responses. Finally, Mito-MSC transplantation yielded significant reductions in joint mineralization, a hallmark of OA progression, as well as improvements in OA-related histological signs, with the lower dose exhibiting better therapeutic efficacy. Furthermore, Mito-MSC was detected within the knee joint for up to 24 h post-injection without eliciting an inflammatory response in CIOA mice. Conclusion Collectively, our results reveal that mitochondria derived from MSC are transferred to key articular cells and are retained in the joint without generating an inflammatory immune response mitigating articular cartilage degradation in OA, probably through a restorative effect triggered by the stress antiviral response within OA chondrocytes.